1970
DOI: 10.1002/chin.197047187
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ISOMERISIERUNG 3‐SUBSTITUIERTER INDOLE, BENZOFURANE UND BENZOTHIOPHENE

Abstract: Die 3‐Methyl‐ bzw. 3‐Phenyl‐indole, ‐benzofurane und ‐benzothiophene (I) gehen bei 15 ‐420minütiger Erwärmung mit Pyrophosphorsäure auf 100 bis 150°C in die 2‐substituierten Isomeren (IV) (Ausbeute 10‐90%) über.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Although 5-OHRA was first synthesized by Grese et al (37), we used a different synthetic procedure. The synthesis of differently substituted benzo[b]thiophene moieties was performed by the cyclization rearrangement induced by PPA, which has been described in the literature by Kost et al (38).…”
Section: Discussionmentioning
confidence: 99%
“…Although 5-OHRA was first synthesized by Grese et al (37), we used a different synthetic procedure. The synthesis of differently substituted benzo[b]thiophene moieties was performed by the cyclization rearrangement induced by PPA, which has been described in the literature by Kost et al (38).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the action of trifluoroacetic acid or polyphosphoric acid on the 2-acyl derivatives of these heterocycles led to intramolecular isomerization to the corresponding 3-isomers and of the 3-alkyl and 3-aryl derivatives to the 2-isomers [75][76][77]. It was found that the action of trifluoroacetic acid or polyphosphoric acid on the 2-acyl derivatives of these heterocycles led to intramolecular isomerization to the corresponding 3-isomers and of the 3-alkyl and 3-aryl derivatives to the 2-isomers [75][76][77].…”
Section: Five-membered Heterocycles With One Heteroatom and Their Conmentioning
confidence: 99%
“…1,3132 The mechanism is widely thought to involve concomitant cyclization and 1,2 aryl ring migration. The regioisomers in this example result from initial cyclization occurring either ortho or para to the methoxy group on the aryl ring of the sulfide.…”
Section: Introductionmentioning
confidence: 99%
“…The regioisomers in this example result from initial cyclization occurring either ortho or para to the methoxy group on the aryl ring of the sulfide. 1,3132 …”
Section: Introductionmentioning
confidence: 99%